Economic Activities of Klepon Buntut Bukhari - Muhammad Risalan Uzhma; Mutiani Mutiani; M. Ridha Ilhami; Raihanah Sari; Sigit Triyono (Universitas Lambung Mangkurat, 2024)
This article discusses the economic activities of Klepon Buntut Bukhari business owners in Jawa Village and Sekumpul Village. This research was conducted to describe the economic activities of Klepon Buntut Bukhari business actors with an in-depth discussion on distribution activities. Jawa Village RT 01 RW 05 and Sekumpul Village RT 01 RW 01 became the research locations. Qualitative approach with descriptive method with data collection through observation, interviews and documentation. Data analysis by detailing, expressing and verifying data. Data validity using extended observation, member check, and triangulation of sources, techniques and time. The results of the study state that the economic activities of Buntut Bukhari Klepon business actors with production activities in general in the form of preparation and making Klepon and consumption activities with Klepon consumers from road users with most of the teenage and adult age groups, while Klepon distribution activities are carried out by visiting road users directly and by setting up stalls on the side of the road with the aim of distributors to make it easier for consumers to get Klepon and for distributors for daily needs.